2015
DOI: 10.1182/blood-2015-01-623975
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells accumulate in the bone marrow of myeloma patients where they protect tumor plasma cells from CD8+ T-cell killing

Abstract: Key Points• Dendritic cells accumulate in the bone marrow of multiple myeloma patients.• Bone marrow dendritic cells play a dual, but opposing, role in multiple myeloma.Many researchers have speculated that the clinical progression from monoclonal gammopathy of undetermined significance (MGUS) to multiple myeloma (MM) is driven by defects in dendritic cell (DC) function. However, evidence supporting this assumption is controversial, and no mechanism for the putative DC dysfunction has been demonstrated thus fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
96
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(103 citation statements)
references
References 35 publications
(40 reference statements)
6
96
0
1
Order By: Relevance
“…It has been recently recognized that both patients with MGUS and those with MM have, in the bone marrow, tumor-specific CD8 + T cells that are, however, unable to limit the expansion of the malignant plasma cells. [2][3][4][5] Tumor-specific CD8 + T cells flooding into the bone marrow initially encounter endothelial cells (EC) that line the bone marrow microsinusoids. Trafficking of CD8 + T cells between blood and bone marrow is facilitated by the discontinuous basement membrane and the EC fenestrations of sinusoids.…”
Section: Introductionmentioning
confidence: 99%
“…It has been recently recognized that both patients with MGUS and those with MM have, in the bone marrow, tumor-specific CD8 + T cells that are, however, unable to limit the expansion of the malignant plasma cells. [2][3][4][5] Tumor-specific CD8 + T cells flooding into the bone marrow initially encounter endothelial cells (EC) that line the bone marrow microsinusoids. Trafficking of CD8 + T cells between blood and bone marrow is facilitated by the discontinuous basement membrane and the EC fenestrations of sinusoids.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] They are recruited by MM cells to create a localized immunosuppressive niche for MM survival. OCs are terminally differentiated cells of the monocyte/macrophage lineage with similar immune receptors in the innate immune system.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been shown that pDC confer a growth and survival advantage to MM cells . More precisely, the pDC antitumor function, through the decrease of cytotoxic CD8 T‐cell activation, is abolished by MM cells . Therefore, the decreased number of pDC associated with the use of Dara suggests an additional mechanism of action of Dara through pDC depletion.…”
Section: Discussionmentioning
confidence: 99%
“…19 More precisely, the pDC antitumor function, through the decrease of cytotoxic CD8 T-cell activation, is abolished by MM cells. 20 Therefore, the decreased number of pDC associated with the use of Dara suggests an additional mechanism of action of Dara through pDC depletion. Recently, Chen et al 12 demonstrated that CD38 upregulation in tumors induces resistance to PD-1/PD-L1 blocking antibodies and coinhibition of CD38 and PD-L1 improves antitumor immune response.…”
Section: Discussionmentioning
confidence: 99%